A Survey of the Multifaceted Implications of Bullying and Victimisation among Some Secondary Schools in Southern Nigeria - Dorothy Mma Afunugo (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Bullying and victimization in schools pose significant threats to students' psychological well-being, academic performance, and overall school climate. In Southern Nigeria, the prevalence and implications of such behaviors require deeper exploration to inform appropriate interventions. Objective: This study aimed to investigate the multifaceted implications of bullying and victimization among secondary school students in Southern Nigeria, focusing on the perspectives of teachers regarding its impact and mitigation strategies. Method: A descriptive research design was employed, with data collected in June 2024 through a convenience sample of secondary school teachers from the region. Participants completed a web-based survey using the validated 42-item Bullying and Victimization Scale (BVS), which measured variables such as age, gender, teaching experience, and educational background. The BVS demonstrated strong reliability, with a Pearson correlation coefficient of r = 0.81 across two administrations. Data were analyzed using descriptive statistics and correlational methods, including Spearman’s rho and Kendall’s tau-b. Result:The findings revealed widespread incidents of bullying and victimization in secondary schools, significantly affecting students’ mental health and academic engagement. Teachers reported a need for improved preventive measures and support structures within schools. Conclusion: Bullying and victimization remain pressing issues in Southern Nigerian secondary schools, necessitating comprehensive interventions to foster safe and supportive educational environments. Contribution: This study underscores the urgency of implementing robust anti-bullying policies, increasing staff supervision, and integrating social-emotional learning into the curriculum. The findings offer actionable insights for educators, policymakers, and stakeholders committed to promoting student welfare and academic success.